Performance of Alternative Peat Cement Brick as Construction Material - Jaffar, Nur Liyana; Wan Jusoh, Wan Amizah; Syed Mohd Fareed, Syed Zin; Nurul Hidayah, Roslan (Progress in Engineering Application and Technology, 2023)
Sustainable Development Goals (SDG) are the strategy for ensuring a more prosperous and sustainable future for all communities. Based on the goals that require actions by all developing countries, the focus is now on evolving and producing building materials that are sustainable by utilizing various types of waste. Open-dumping landfills, greenhouse gas and carbon dioxide emissions, industry demands for sustainable materials, and the downsides of current bricks such as low durability are the issues that need to be resolved. Hence, the production of eco-brick that utilize waste peat soil could be the alternative to minimize these problems. In this study, 60 samples of alternative peat cement bricks were tested for their mechanical properties with various percentages of peat soil replacement starting with 5%, 10%, 15%, and 20%. All laboratory testing such as compressive strength, density, water absorption, UPV, and thermal conductivity was conducted at Universiti Tun Hussein Onn Malaysia Batu Pahat campus and Pagoh Campus. It was observed that bricks with 15% peat soil produced a high-dense brick with the highest compressive strength, and has a minimal defect. Meanwhile, the higher the percentage of peat soil in cement brick, the higher the water absorption rate. Bricks that contain 5% of peat soil recorded the lowest K-value compared to other bricks with peat soil. It can be concluded that peat soil is significant to the mechanical properties of cement brick. This alternative peat cement brick is eligible as a construction material based on standard requirements.